(untitled) (Indian Journal of Chemistry (IJC), 2024)
In this work, we have design and synthesis of water-soluble phosphonate containing chromophore. As-prepared compound phosphonate-naphthalimide-morpholine (NPI-M-P2) was investigated for their photophysical by means of UV-Vis and fluorescence spectroscopy at different pH ranging from 2 to 10. Upon excitation of absorption band at 410 nm, NPI-M-P2 exhibits strong fluorescence emission peak maxima at 565 nm. With the increase in pH from 3 to 9, emisison peak intensity of NPI-M-P2 was increased and displayed brighter green color.